Auditory and visual cueing modulate cycling speed of older adults and persons with Parkinson's disease in a Virtual Cycling (V-Cycle) system. Issue 1 (December 2016) - Gallagher, Rosemary; Damodaran, Harish; Werner, William; Powell, Wendy; Deutsch, Judith
Abstract Background Evidence based virtual environments (VEs) that incorporate compensatory strategies such as cueing may change motor behavior and increase exercise intensity while also being engaging and motivating. The purpose of this study was to determine if persons with Parkinson's disease and aged matched healthy adults responded to auditory and visual cueing embedded in a bicycling VE as a method to increase exercise intensity. Methods We tested two groups of participants, persons with Parkinson's disease (PD) (n  = 15) and age-matched healthy adults (n  = 13) as they cycled on a stationary bicycle while interacting with a VE. Participants cycled under two conditions: auditory cueing (provided by a metronome) and visual cueing (represented as central road markers in the VE). The auditory condition had four trials in which auditory cues or the VE were presented alone or in combination. The visual condition had five trials in which the VE and visual cue rate presentation was manipulated. Data were analyzed by condition using factorial RMANOVAs with planned t-tests corrected for multiple comparisons. Results There were no differences in pedaling rates between groups for both the auditory and visual cueing conditions. Persons with PD increased their pedaling rate in the auditory (F 4.78, p  = 0.029) and visual cueing (F 26.48, p  < 0.000) conditions. Age-matched healthy adults also increased their pedaling rate in the auditory (F  = 24.72, p  < 0.000) and visual cueing (F  = 40.69, p  < 0.000) conditions. Trial-to-trial comparisons in the visual condition in age-matched healthy adults showed a step-wise increase in pedaling rate (p  = 0.003 top  < 0.000). In contrast, persons with PD increased their pedaling rate only when explicitly instructed to attend to the visual cues (p  < 0.000). Conclusions An evidenced based cycling VE can modify pedaling rate in persons with PD and age-matched healthy adults. Persons with PD required attention directed to the visual cues in order to obtain an increase in cycling intensity. The combination of the VE and auditory cues was neither additive nor interfering. These data serve as preliminary evidence that embedding auditory and visual cues to alter cycling speed in a VE as method to increase exercise intensity that may promote fitness.